Future data and security engineering : Second International Conference, FDSE 2015, Ho Chi Minh City, Vietnam, November 23-25, 2015 : proceedings /: Second International Conference, FDSE 2015, Ho Chi Minh City, Vietnam, November 23-25, 2015 : proceedings. (2015) - Unknown
No abstract available